The Contribution of Contemporary African American Literature in American Society - Lakehal , Fatiha; Naoumi ,Mohamed (Faculty of Letters and Foreign Languages Department of English, 2019)
African American people among the other societies suffered severely from earlier time because of their terrifying past that affected them negatively. Actually their suffering resulted from their historical background since slavery, racism and exploitation that destroyed the Black society. In this context, those experiences inspired African American authors to write on those experiences. As a result, they succeeded in creating a distinct literature which has become accepted as an integral part of American literature .Whereas other views denied this literature as one of inferiority which should disappear. Hence, African American writers have struggle to defend their cultural and literary heritage by highlighting positively the African American’s reality, portraying different themes. However, the black literature has confronted a bitter disappointment by new critiques that discussed again its location in American literature. This work is an attempt to describe the African American literature in American Society and its recent developments in which it relies on commentaries on number of related texts